Preeclampsia-eclampsia and future cardiovascular risk among women in Taiwan - Yu-Ling Kuo; Te-Fu Chan; Chien-Yi Wu; Chin-Ru Ker; Hung-Pin Tu (Elsevier, 2018)
Objective: This study aims to examine the long-term cardiovascular and cerebrovascular risks in a large cohort of women with past history of preeclampsia and/or eclampsia. Materials and methods: This is a retrospective longitudinal study using National Health Insurance Research Database from 1996 to 2010. We identified 1295 women with preeclampsia and eclampsia. The control group was 5180 pregnant women without preeclampsia/eclampsia, who were matched for age and date of delivery. The incidences of diabetes, dyslipidemia, hypertension and cardiovascular events after pregnancy were identified from medical records after the date of delivery to the date of an event or the end of the study. Results: The median follow-up duration was 9.8 years (interquartile 5.1-12.7 years). The incidences of diabetes, dyslipidemia, hypertension, congestive heart failure and cerebrovascular disease events were significantly greater in women with eclampsia or preeclampsia than those in controls. Eclampsia or preeclampsia increased the risk of diabetes, dyslipidemia, hypertension, congestive heart failure and cerebrovascular disease events (hazard ratio [HR] 3.84 and 5.42, P < 0.0001; HR 2.75 and 3.40, P < 0.0001; HR 6.52 and 7.31, P < 0.0001; HR 9.07, P = 0.0060 and 7.39, P < 0.0001; HR 10.71, P < 0.0001 and 3.47, P = 0.0048, respectively). The survival curves for the development of congestive heart failure and cerebrovascular disease in women with eclampsia/preeclampsia and in control differed significantly (Log-rank test P < 0.0001). From the curve, we can find dramatic increases of congestive heart failure and cerebrovascular disease incidences at roughly 3 years and 10 years since the diagnosis of eclampsia/preeclampsia. Conclusions: Our study revealed that women with a history of preeclampsia/eclampsia were at increased risks for subsequent diagnoses of diabetes, dyslipidemia, hypertension, congestive heart failure and cerebrovascular disease. Preventive counseling, more vigilant screening and management for the modifiable risks should be provided to the affected women. Clinicians should closely monitor these patients in the first three years postpartum and continuously for up to at least a decade.